The trend of recidivism in Iowa / Nur Syahida Sahirah Nor Zainal, Puteri Khalidah Mastor and Nurul Amirah Ahmad Mohsen - Nor Zainal, Nur Syahida Sahirah; Mastor, Puteri Khalidah; Ahmad Mohsen, Nurul Amirah (2019)
Recidivism can be defined as act repeating or return to the criminal behaviour by the same or different type of offense. A recidivist refers to a person that commits crimes again after being released from prison. The focus of this study is to examine the trend of recidivism in Iowa. This study aims to determine the common race that does recidivism, the average day for the criminal to commit crime again after release, and to find out whether all the recidivists do the same type of crimes for the first and second times. In addition, this study examined the relationship between age of release for the first time and number of days recidivists take to commit crime again. In this study, the researchers used descriptive, normality and non-parametric tests as the methodology. Descriptive statistics were used to determine the normality of distribution. This method was used to achieve the first, second and third objectives in this study. Next, normality and non-parametric tests were used to fulfil the last objective of the study. The study found that recidivism is commonly done by Blacks rather than Whites and most of the recidivists repeat the same crime again after being released from their first imprisonment within 13 months. Finally, there is a significant relationship between age of release for the first imprisonment and number of days recidivists take to commit crime again. For future studies, it is recommended for researchers to look into local data to better explain the trend of recidivism in the Malaysian context.